Identification of health beneficial chemical constituents from the hydrosol and condensate of Aquilaria Malaccensis prior soaking: article / Mohd Azizi Husaini and Nurhaslina Che Radzi - Husaini, Mohd Azizi; Che Radzi, Nurhaslina (2017)
Agar wood (Aquilaria Malaccensis) is a fragrant wood containing economically important essential oil. It has been traded for many purposes including for incense, perfume and traditional medicine. However, the byproduct after hydro distillation which known as distillate (hydrosol) and condensate are, considered as waste. Therefore, this research was aimed to identify the remaining beneficial compounds that present in the hydrosol and condensate after hydro distillation rather than to be disposed. Mostly researchers are focused on analyzing the chemical constituent in essential oil only rather than the hydrosol and condensate. These agar wood bulks are much expensive in market so more study is compulsory on analyzing the content of hydrosol and condensate as well as the essential oil. Before hydro distillation process is carried out towards the agar wood, soaking process were conducted as pretreatment by varies its pH condition from acidic to base (pH 3, 4, 7, 11 and 12) at 25 oC. The soaking duration was standardized and set for one week for all samples. 100 g of grinded agar wood was put in the round bottom flask to run hydro distillation process by using 800 ml of distilled water as solvent. The hydrosol and condensate sample were taken after nine hours run through hydro distillation. Thermogravimetric analysis (TGA) was conducted to evaluate organic loss in the chips after being hydrolyzed. The condensate and distillate samples were analyzed with Gas Chromatography Mass Spectroscopy (GC-MS) to detect the compounds present. The result showed that the most suitable soaking condition for agar wood is at pH 3 with acidic condition. Analyzing by using GC-MS had shown that the composition of compound present after hydro distillation process was differed from each condition of soaking water.